1993
DOI: 10.7863/jum.1993.12.7.403
|View full text |Cite
|
Sign up to set email alerts
|

Color flow sonographic mapping of intravascular extension of malignant renal tumors

Abstract: ble role of CDFI in identifying malignant renal tumor thrombus in the renal vein or the IVC. This study involved 24 tumors in 23 patients, including 19 renal cell carcinomas, four Wilms' tumors, and one rhabdoid tumor. CDFI had an overall sensitivity of 95% in predicting combined renal vein and IVC tumor in· volvement but was more sensitive in the renal vein alone (100%) than in the IVC alone (89% ). Specificity of CDFI was nearly equal for both renal vein and IVC A ccurate preoperative staging of malignant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Ultrasound with Doppler was the most commonly used (94%), and has been proven to be effective and reliable and has the benefit of being able to be used intraoperatively if required. [ 6 7 8 9 ] The second most popular imaging modality used was computed tomography (CT) (76%), which is routinely used in the staging of patients with Wilms’, although the sensitivity to identifying tumor thrombus is noted to be less as is the accuracy of determining the level of thrombus extension[ 6 ] [Figures 2 and 3 ]. Twelve percent of the group had venography, where the level of extension of the tumor thrombus remained unclear.…”
Section: Preoperative Identification Of Intravascular Thrombusmentioning
confidence: 99%
“…Ultrasound with Doppler was the most commonly used (94%), and has been proven to be effective and reliable and has the benefit of being able to be used intraoperatively if required. [ 6 7 8 9 ] The second most popular imaging modality used was computed tomography (CT) (76%), which is routinely used in the staging of patients with Wilms’, although the sensitivity to identifying tumor thrombus is noted to be less as is the accuracy of determining the level of thrombus extension[ 6 ] [Figures 2 and 3 ]. Twelve percent of the group had venography, where the level of extension of the tumor thrombus remained unclear.…”
Section: Preoperative Identification Of Intravascular Thrombusmentioning
confidence: 99%
“…Color Doppler sonography has been used to assess intravascular extension of malignant renal tumors [6,7], but has limitations such as its inability to predict venous tumor extension in large or bulky tumors [3]. Before the advent of MR, CT proved to be the most reliable and sensitive technique for staging renal cell carcinoma [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 100% sensitivity for renal vein involvement and 89–100% sensitivity for inferior vena caval involvement have been reported [8, 10]. Habboub et al [8]reported a retrospective study on Doppler sonography examination of 39 patients with renal masses and found a sensitivity of 75% for renal vein and 100% for vena cava thromboses with a specifity of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler sonography is a frequently used diagnostic tool in urology and has recently been introduced into the examination of renal masses. Few reports in the literature describe the role of color/duplex sonography showing an up to 100% sensitivity for renal and 89–100% sensitivity for inferior vena caval involvement [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%